Analisis penilaian Kinerja Karyawan Menggunakan metode Behaviorally Anchore Rating Scale BARS dan Management By Objectives MBO Di CV Brilliant - Abdul Latif Harahap; Surya Perdana (Universitas Persada Indonesia YAI, 2021)
CV. Brilliant is a manufacturing company engaged in the convection industry in themanufacture of various types of clothing, namely shirts, t-shirts, school uniforms and officeuniforms. In running its business where there are complaints from production employees on workreports regarding performance appraisals that do not have measurable standards so thatperformance appraisals tend to be subjective, and there is no target and reciprocity on employeeperformance achievements so that employees feel uncomfortable and unmotivated at work whichresults in decreased production in the period from January to June 2019. The purpose of thisstudy is to find out the causes of the decline in employee performance and solutions to increaseemployee productivity, the researchers analyzed using the Behaviorally Anchor Rating Scale(BARS) and Management By Objectives (MBO) methods using SPSS software. From the resultsof the analysis obtained several factors in the performance appraisal including Personality worth5,167, Work Behavior 2,069, Quality of work 1,825, Reliability 1,355 work and Managerial1,028 as well as the existence of standard goals and reciprocity for employees in performance appraisal to increase productivity. Using both methods can solve performance appraisal problemsso that employees can work comfortably and full of motivation.